Alphabet learning center activities kit - Fetzer, Nancy (Center for Applied Research in Education, 2000)
This practical resource gives primary teachers a collection of stimulating, tested learning center activities to teach and reinforce alphabet letters and their sounds. Helps children identify and spell words with ease!